2016
DOI: 10.14742/ajet.2787
|View full text |Cite
|
Sign up to set email alerts
|

Discursive constructions of teacher in an educational technology journal

Abstract: The integration of technology with teaching and learning is a significant area of research in the educational technology field. Teachers play an instrumental role in technology integration, and many teacher-related factors have been identified that predict technology use and integration in educational settings. How teachers are represented in the educational technology literature (e.g., as caring, didactic or lazy) can potentially impact on how technology integration takes place. However, there is little resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…These reflected the growing "international focus of the journal" (Hadlock et al, 2014, p. iv). They were also similar to the AJET corpus analysis findings of McDonald and Loke (2016), which analysed articles from 1991-2014, and found that the top 10 most frequent words included: students, learning, technology, online, teachers, and teaching.…”
Section: In Their Analysis Of the British Journal Of Educational Techsupporting
confidence: 77%
See 2 more Smart Citations
“…These reflected the growing "international focus of the journal" (Hadlock et al, 2014, p. iv). They were also similar to the AJET corpus analysis findings of McDonald and Loke (2016), which analysed articles from 1991-2014, and found that the top 10 most frequent words included: students, learning, technology, online, teachers, and teaching.…”
Section: In Their Analysis Of the British Journal Of Educational Techsupporting
confidence: 77%
“…One major shift in focus during the past five years has been the focus in articles on "computer/technology uses in education" and "student learning" (Table 4), which echoes the findings by McDonald and Loke (2016) in their corpus analysis of AJET, and which has also occurred in the wider field of educational technology. Marin et al (2018) analysed 221 articles from the IJETHE between 2010-2017 and found that research had moved from focusing on technology and tools, to focusing more on how they could be used to foster student learning and competencies, so too Zawacki-Richter and Latchem (2018) in their analysis of CAE.…”
Section: Keyword and Abstract Analysismentioning
confidence: 65%
See 1 more Smart Citation
“…Research published in AJET in 2013-2017 has become more student-centred (Bond & Buntins, 2018), focusing in particular on teacher knowledge and skill development to strengthen teaching and learning, as well as on collaborative learning in online environments, echoing a previous analysis of AJET (McDonald & Loke, 2016) and research in the wider educational technology field (e.g., Marin, Duart, Galvis, & ZawackiRichter, 2018;Zawacki-Richter, et al, 2017;Zawacki-Richter & Latchem, 2018). AJET publications during this period used a relatively even mix of inferential, interpretative, and combined methods (Bond & Buntins, 2018), showing less methodological bias than in other educational technology journals (Perez-Sanagustin, et al, 2017;.…”
Section: Ajet In Previous Bibliographic Studiesmentioning
confidence: 97%
“…Aside from the analyses by Bond and Buntins (2018), McDonald and Loke (2016) and Hadlock et al (2014), AJET editors also provide yearly bibliometric analyses (e.g., Dalgarno, Heinrich, & Henderson, 2016), which provide submission and review statistics, publication summaries, the most downloaded articles, and citation information. Article submissions continue to grow, which has meant a larger number of rejections at both stages of the review process (Heinrich, Lee, & Henderson, 2017).…”
Section: Ajet In Previous Bibliographic Studiesmentioning
confidence: 99%